2017
DOI: 10.1002/bmb.21090
|View full text |Cite
|
Sign up to set email alerts
|

Lego bricks and the octet rule: Molecular models for biochemical pathways with plastic, interlocking toy bricks

Abstract: The 8 studs on a 2 3 4 Lego brick conveniently represent the outer shell of electrons for carbon, nitrogen, and oxygen atoms. We used Lego bricks to model these atoms, which are then joined together to form molecules by following the Lewis octet rule. A variety of small biological molecules can be modeled in this way, such as most amino acids, fatty acids, glucose, and various intermediate metabolites. Model building with these familiar toys can be a helpful, hands-on exercise for learning-or relearning-bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
0
11
0
2
Order By: Relevance
“…Outra alternativa que pode ser enquadrada no quesito jogos, é o uso de blocos de construção tipo lego. Lin et al, (2018), usaram modelos de blocos Lego em programas de pós-graduação em residência em pediatria e genética médica para revisar tópicos das vias bioquímicas. O uso de modelos Lego forneceu uma representação prática de moléculas envolvidas em importantes desordens bioquímicas, como, erros inatos do metabolismo.…”
Section: Estrutura E Função De Uma Proteína Hipotéticaunclassified
See 1 more Smart Citation
“…Outra alternativa que pode ser enquadrada no quesito jogos, é o uso de blocos de construção tipo lego. Lin et al, (2018), usaram modelos de blocos Lego em programas de pós-graduação em residência em pediatria e genética médica para revisar tópicos das vias bioquímicas. O uso de modelos Lego forneceu uma representação prática de moléculas envolvidas em importantes desordens bioquímicas, como, erros inatos do metabolismo.…”
Section: Estrutura E Função De Uma Proteína Hipotéticaunclassified
“…O uso de modelos Lego forneceu uma representação prática de moléculas envolvidas em importantes desordens bioquímicas, como, erros inatos do metabolismo. O resultado deste trabalho resumiu-se a apenas ao entusiasmo dos envolvidos com a revisão de vias bioquímicas (LIN et al, 2018). Outros mecanismos auxiliares também foram utilizados para aprofundar as habilidades necessárias de visualização molecular das proteínas (DRIES et al, 2017).…”
Section: Estrutura E Função De Uma Proteína Hipotéticaunclassified
“…Several simple molecular models can be constructed, employing a 1 × 2 white brick, as a hydrogen atom. Similarly, 2 × 4 grey, blue, and red bricks can be employed as carbon, nitrogen, and oxygen atoms, respectively ( Figure 5a) (Lin et al, 2018). However, when teachers try to represent large molecules, the corresponding LEGO models tend to be long (Figure 5b).…”
Section: Bond Order and The Octet Rulementioning
confidence: 99%
“…Active learning approaches improve student engagement, learning, motivation, autonomy, curiosity, interaction, attention, and performance (5,(17)(18)(19)(20). A variety of active learning tools such as software, games, and web-based learning (15,(21)(22)(23)(24)(25)(26)(27)(28), scientific articles (22,29,30), flipped jigsaw activities (16), guided practices (31,32), problem-based learning (31,33), and physical models (11,(34)(35)(36)(37)(38) have been used to improve biochemistry, cell metabolism, and physiology knowledge of students in a small, medium, and large-group classroom setting.…”
Section: Introductionmentioning
confidence: 99%
“…Physical models are a potential teaching tool to make a biological phenomenon more "visible" and less abstract, assisting professors and students in overcoming the challenges associated with the teaching-learning process of different molecular concepts and mechanisms (5,9,38). The use of physical models resulted in the improvement of learning of themes related to macromolecules, protein structure and function (35,36,39,40), the central dogma of molecular biology (5), membrane potential and action potential (11), skeletal muscle physiology (37), and the demonstration of factors affecting the glomerular filtration rate (34). These and other studies also reported that the use of physical models stimulated the students to construct their knowledge as well as improve their critical thinking skills.…”
Section: Introductionmentioning
confidence: 99%